PELATIHAN PENGAWAS OPERASIONAL PERTAMA (POP) PERTAMBANGAN DALAM MENDUKUNG KINERJA KESELAMATAN PERTAMBANGAN DI PT TIMAH - Arif Budiyono (PPSDM Geominerba, 2021)
The implementation of the Mining Frontline Operational Supervisor training at PT Timah which is focused and effective in fulfilling all aspects of the competency dimensions, both in terms of knowledge, skills and attitudes, greatly affects the achievement of learning outcomes and the impact of training on the organization in order to improve mining safety performance The Mining Frontline Operations Supervisor training program at PT Timah organized by the Center for Geological, Mineral, and Coal Human Resources Development was able to achieve an adequate level of success in providing the fulfillment of performance capabilities for all competency units of Mining Frontline Operations Supervisor. In the training aspect, generally have a positive perception in all aspects of training instructional design including training curriculum and syllabus, training materials, and training infrastructure. The results of tracing interview and observation instruments on several important indicators in the competency unit of Mining First Operations Supervisor in supporting Mining safety performance such as the implementation of inspection, implementation of job safety analysis, and implementation of planned mining safety meetings provide adequate results for all required criteria both from the perspective competency test and evaluation of learning outcomes.